(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study discussed the legal regulation Protection for the design of the integrated service under the patent system and the planning designs of the Saudi Integrated Service. It followed the analytical approach by reviewing legal texts on substantive and formal design requirements to justify systematic protection, procedures for applying for a certificate of protection and identifying the legal provisions contained therein; In order to achieve the study’s objectives of clarifying what is meant by integrated management and enumerating the design requirements for systematic protection, as well as the procedures required by the regulator for requesting protection, the integrated service is one of the much-needed industries, which is critical to its high efficiency compared to its small size. The study found several findings, most notably: the Saudi regulator deliberately delved into the technical composition of the design of the Integrated Service when defined as a technical issue and not a legal situation or situation, the applicant or the authorized person must apply to the competent authority for a certificate of protection whenever his design is real, applicable to the industry and not contrary to sharia law. The study also recommended several recommendations, including: the Saudi regulator must explicitly stipulate the design requirement for industrial applicability of the regime’s protection entitlement.